Serum presepsin level reflects macrophage activation and hemophagocytosis in bone marrow - Katsumasa Yamanaka; Kazuki Furuhashi; Kumiko Shimoyama; Yusuke Okubo; Toshitaka Yukishima; Saori Sawada; Miwa Adachi; Keita Yamashita; Moriya Iwaizumi; Yasuyuki Nagata; Takaaki Ono; Noriyoshi Ogawa; et al. (PLoS ONE, 2026)
Background Presepsin (soluble CD14 subtype) is a clinically used diagnostic biomarker for sepsis. It is secreted into the blood by activated macrophages, and serum concentrations are elevated in patients with sepsis. Previous reports suggest that presepsin may be secreted into the peripheral blood due to increased hemophagocytosis. However, the relationship between serum presepsin concentration and hemophagocytosis, as evidenced by bone marrow aspiration for diagnosing hemophagocytic lymphohistiocytosis, is not well understood. Therefore, we investigated the relationship between serum presepsin level and hemophagocytes in bone marrow. Methods We retrospectively analyzed 61 patients with serum presepsin level who underwent bone marrow aspirations. We examined the relationship between serum presepsin level and other laboratory findings, including the number of macrophages and the percentage of hemophagocytes in their bone marrow. Macrophages and hemophagocytes were counted using bone marrow smears. Immunostaining of bone marrow aspirate smears was performed using a CD14 antibody to evaluate the relationship between serum presepsin level and hemophagocytes in the bone marrow. Results Serum presepsin level correlated with inflammatory markers (C-reactive protein and D-dimer) and markers related to hemophagocytosis (lactate dehydrogenase, ferritin, red blood cell count, hemoglobin, hematocrit, number of macrophages, and percentage of hemophagocytes in the bone marrow). The percentage of hemophagocytes in the bone marrow was positively correlated with serum presepsin level (r = 0.435, p < 0.001) and with ferritin (r = 0.438, p = 0.015), both of which were elevated during hemophagocytosis. CD14 expression is attenuated in hemophagocytes in bone marrow and lymph nodes. Conclusion These findings suggest that serum presepsin is released by hemophagocytes and reflects the activation of macrophages and hemophagocytosis in bone marrow.